Nanotechnology-Driven Water Purification Systems for Sustainable Irrigation in Arid Regions - Vij Priya; Kumaraswamy Balasubramaniam (SHS Web of Conferences, 2025)
Since nanotechnology has emerged as one of the most developed technologies in terms of water purification in arid regions and owing to the increasing demand of sustainable irrigation solutions, it has become increasingly important. In this study, the development and optimization of nanotechnology driven water purification systems with operation in arid environments is studied. The focus of this research is the development of nanomaterials-based enhancement of Thin-Film Composite (TFC) membranes in order to obtain superior filtration efficiency, augment flux rates and reduce fouling. Furthermore, Membrane Bioreactor (MBR) systems are integrated into the system to enhance overall water quality by combining biological treatment with advanced filtration, leading to cost reduction of operations. Total Organic Carbon (TOC) sensors give real time monitoring and provide crucial data for the management of water quality and to ensure good performance of the system. Support Vector Regression (SVR) and Principal Component Analysis (PCA) increase the accuracy of predictive capabilities and optimizes the operations. These technologies are integrated and represent a major step in achieving water scarcity challenges for irrigation in water stressed areas with integrated approach. It was shown that the optimized TFC membranes achieved a flux rate of 25.5 L/m2•h, a specific permeability of 19.2 L/m2 bar•h and decrease in membrane fouling rate to 0.011 mg/cm2h. A transmembrane pressure drop of 0.24 bar was found to be the average. Although SVR and PCA have been used to analyze system data, after applying data analysis with SVR and PCA, system efficiency is improved by 18%, and the performance predictions made are accurate enough for system management and operational adjustment. Techniques used in Typical IFH MBR studies and terms: Thin Film Composite (TFC), Membrane Bioreactor (MBR) systems, Total Organic Carbon (TOC), Support Vector Regression (SVR) and Principal Component Analysis (PCA).